The Uses of Human Malleability: Images of Hellish and Heavenly Sojourns in Pre-Modern Burma - Handlin, Lilian (Religions (Basel, Switzerland ), 2020)
For more than a millennium, Burmese donors sponsored elaborately decorated structures to publicize their allegiance to the Buddha’s Dhamma in its Pali version, illuminating their understanding of the human predicament. The structures always featured décor informed by revered texts, the Buddha’s words or Buddhavacana and its elaborators, that in the context of the biography of Gotama Buddha writ large, recalled numerous sub-chapters en route to Awakening. Throughout that immensely long timeframe, conceptions of retribution, recalling sojourns in various hells or heavenly mansions, remained constant. Their interpretation, however, moved with the times, reflecting the ever-shifting components of the Gotama saga designed to meet changing circumstances. The article explains why and how these two subjects sustained their influence, how their meanings changed, and how their visual interpretation reflected contemporaries’ grasp of the future. The core argument asserts that behind the images was a socializing conditioning mechanism revealing this setting’s ideational substructure. That substructure’s lineaments exploited psychological and physiological assumptions regarding how humans functioned, harnessing emotions evoked by stories and images and utilizing fear as a form of societal control. The aim was to create what throughout Burmese history were called “the good people”—ideal subjects for a dhamma-governed society.